2003
DOI: 10.1002/ch.277
|View full text |Cite
|
Sign up to set email alerts
|

On the efficacy of hypnosis: a meta‐analytic study

Abstract: From 444 studies published until 2002 that investigated the efficacy of hypnosis, 57 randomized clinical studies were selected that compared patients treated exclusively by hypnosis to an untreated control group (or to a group of patients treated by conventional medical procedures). The 57 studies were integrated into a meta-analysis that yielded a weighted average post-treatment effect size of d = 0.56 (medium effect size). For hypnotic treatment of ICD-10 codable disorders (32 studies) the calculation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 73 publications
1
37
0
1
Order By: Relevance
“…Hypnosis is typically used as an adjunctive intervention that supplements or is weaved into another treatment and it is most advantageous when implemented to enhance the effectiveness of an already established empirically supported approach. For example, a meta-analysis of 18 studies found that the average client receiving cognitive-behavioral hypnotherapy displayed greater improvement than at least 70% of clients receiving the same non-hypnotic cognitive-behavioral treatment (Kirsch, Montgomery, & Sapirstein, 1995 (Flammer & Bongartz, 2003). There is also evidence for superior outcomes for hypnosis than control treatment in outcomes related to surgical patients (20 studies) (Montgomery, David, Winkel, Silverstein, & Bovbjerg, 2002) and surgical or medical patients (34 RCTs) (Tefikow et al, 2013), reduced nausea and vomiting in patients undergoing chemotherapy (6 RCTs) (Richardson et al, 2007), and reduced needle-related pain and distress in children and adolescents (7 trials) (Birnie et al, 2014).…”
Section: Evidence Base For the Therapeutic Efficacy Of Hypnosismentioning
confidence: 99%
“…Hypnosis is typically used as an adjunctive intervention that supplements or is weaved into another treatment and it is most advantageous when implemented to enhance the effectiveness of an already established empirically supported approach. For example, a meta-analysis of 18 studies found that the average client receiving cognitive-behavioral hypnotherapy displayed greater improvement than at least 70% of clients receiving the same non-hypnotic cognitive-behavioral treatment (Kirsch, Montgomery, & Sapirstein, 1995 (Flammer & Bongartz, 2003). There is also evidence for superior outcomes for hypnosis than control treatment in outcomes related to surgical patients (20 studies) (Montgomery, David, Winkel, Silverstein, & Bovbjerg, 2002) and surgical or medical patients (34 RCTs) (Tefikow et al, 2013), reduced nausea and vomiting in patients undergoing chemotherapy (6 RCTs) (Richardson et al, 2007), and reduced needle-related pain and distress in children and adolescents (7 trials) (Birnie et al, 2014).…”
Section: Evidence Base For the Therapeutic Efficacy Of Hypnosismentioning
confidence: 99%
“…This question seems to have been solved thanks to Raz's experiment with the stroop test 6 where he demonstrated that hightly hypnotisable subjects were more likely to short-circuit neuronal networks managing conflicts than less hypnotisable subjects (Raz, 2005). According to a large meta-analysis of 57 controlled trials testing hypnosis (Flammer, 2003), the hypnotic susceptibility was responsible for about 20% of treatment outcomes. This percentage is not negligible but this means that 80% of hypnosis capacities depend on other parameters: this is a reassuring perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analyses, however, are prone to the problem of selective publication of studies reporting positive outcomes. In the present investigation, we therefore employed a variety of methods to test for the presence of publication bias in the data analysed by Flammer and Bongartz (2003). The results suggest that publication bias may have contributed to the effect size estimate by about one third.…”
mentioning
confidence: 92%
“…For these and other reasons, the failsafe N is neither an informative, nor a suffi cient statistic to rule out publication bias (Becker, 2005). Therefore, the purpose of the present investigation was to re-analyse Flammer and Bongartz's (2003) data using methods that are better suited to test for a selective reporting of positive outcomes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation